Stem Rust Resistance in a Geographically Diverse Collection of Spring Wheat Lines Collected from Across Africa - Prins, Renée; Dreisigacker, Susanne; Pretorius, Zakkie; van Schalkwyk, Hester; Wessels, Elsabet; Smit, Corneli; Bender, Cornel; Singh, Davinder; Boyd, Lesley A. (Frontiers in Plant Science, 2016)
Following the emergence of the Ug99 lineage of Puccinia graminis f. sp. tritici (Pgt) a collective international effort has been undertaken to identify new sources of wheat stem rust resistance effective against these races. Analyses were undertaken in a collection of wheat genotypes gathered from across Africa to identify stem rust resistance effective against the Pgt races found in Eastern and Southern Africa. The African wheat collection consisted of historic genotypes collected in Kenya, South Africa, Ethiopia, Sudan, Zambia, Morocco and Tunisia, and current South African breeding lines. Both Bayesian cluster and principal coordinate analyses placed the wheat lines from Sudan in a distinct group, but indicated a degree of genetic relatedness among the other wheat lines despite originating from countries across Africa. Seedling screens with Pgt race PTKST, pedigree information and marker haplotype analysis confirmed the presence of Sr2, Sr36, Sr24, Sr31 and Lr34/Yr18/Sr57 in a number of the lines. A genome-wide association study (GWAS) undertaken with Diversity Arrays Technology (DArT) and stem rust (Sr) gene associated markers and Stem Area Infected (SAI) and Reaction Type (RT) field phenotypes, collected from trials carried out across two seasons in Kenya in 2009 and in South Africa in 2011, identified 29 marker-trait associations (MTA). Three MTA were in common between SAI and RT, with the biggest effect MTA being found on chromosome 6AS. Two wheat lines, W1406 and W6979 that exhibited high levels of adult plant stem rust resistance were selected to generate bi-parental mapping populations. Only the MTA on chromosomes 6AS and 3BS, and the locus Lr34/Yr18/Sr57 were confirmed following QTL mapping. Additional stem rust resistance QTL, not detected by the GWAS, were found on chromosomes 2BS, 2DL, 3DL and 4D.